Effectiveness of a Google Sites-Based Career Information Platform in Enhancing Students’ Career Planning Skill - Lilik Sahal Dzul Fahmi; Mungin Eddy Wibowo; Sinta Saraswati; Sunawan Sunawan (Indonesian Journal of Guidance and Counseling: Theory and Application, 2025)
Students’ lack of readiness to develop appropriate career plans reduces their future employment opportunities. This condition is further compounded by the limited availability of career information and career-related media in schools. Accordingly, teachers and school counselors need to introduce innovative approaches to delivering career information. This study examined the effectiveness of a Google Sites–based career information as the platform model to improve senior high school students’ career planning skills. Employing a quantitative pre-experimental one-group pretest–posttest design, the study involved 72 eleventh-grade students from XI A1 and XI A2 at SMA Negeri 1 Weleri. The sample was selected through purposive sampling. Data were collected using an adapted version of the Career Planning Confidence Scale (CPCS). The hypothesis testing was conducted using a paired-samples t-test. The results indicated a statistically significant difference between pretest and posttest scores in career planning skills, suggesting an improvement following the intervention. Further implications are discussed in the discussion section.